Assessment of the wall heat transfer in 3D-CFD in-cylinder simulations of high performance diesel engines. (September 2017) - Sideri, Matteo; Berton, Andrea; D'Orrico, Fabrizio
Abstract: Heat transfer through the combustion chamber walls affects largely engine efficiency, emissions and engine component thermo-mechanical reliability. As a consequence, a correct estimation of the wall heat fluxes is mandatory. However, due to the complexity of the phenomena involved in the heat transfer mechanism, such an estimation is far from being trivial. The paper proposes a methodology aiming at evaluating wall heat transfer in 3D-CFD in cylinder combustion simulations of current production compression ignition engines. A high performance DICI engine is simulated, operated at part-load and medium revving speed. Particular care is devoted to both the evaluation of the auto-ignition delays and the selection of a heat transfer model able to predict correctly gas-to-wall heat transfer. As for the delays, they are evaluated adopting a validated mechanism for a Diesel surrogate composed by a blend of n–dodecane and m–xylene. As for the heat transfer, two different models are tested: a more "consolidated" one, widely available in commercial CFD codes, and a more recent one, based on an alternative formulation of the thermal law of the wall. Finally, in order to validate the proposed methodology, numerical heat transfer is compared to an experimental target.